Contributions to resource and environmental risk management - Pollard, Simon J. T. (Cranfield University, 2009)
This thesis charts a research journey through the disciplines of waste chemistry, environmental risk assessment, policy analysis and corporate risk governance since award of the candidate’s PhD in 1990. The insights gained present a distinctive perspective on resource and environmental risk management - assessments of risk must reflect our understanding of the science and evidence that supports them; and the protection of public and environmental health, as an overarching motive, requires greater prominence if the confidence of citizens in the Government and industry handling of risk is to be secured. Waste management is risk management and without an understanding of the fundamental science and engineering of wastes and how they behave in the environment, process technologies for their treatment can not be optimised, nor regulatory oversight designed properly to protect public health and the environment. The candidate’s research on the chemical characterisation of complex wastes and their interaction with soils, waters and air, offers a more optimistic assessment of these risks, at least within developed nations. This said, technical assessments of risk are insufficient, in isolation, to secure the confidence of communities, investors, or the wider citizenry. The motives and values of process operators and regulators that oversee operations are as critical as technical demonstrations of environmental safety. The recent contributions in this thesis examine organisational competencies in preventative risk management, specifically within the water sector as it responds to international calls for improved risk governance. In concert, the candidate’s contributions and practical achievements in resource and environmental risk management reported here represent a unique and substantive body of problem-oriented research, directed at reconciling societal unease about waste with our responsibilities for its safe management. Significant insights are made on the reuse of hazardous and carbonaceous wastes, on the characterisation, fate and transport of hydrocarbons in the environment, on the practice of environmental risk assessment and the organisational competencies required to manage risk to the levels of stakeholder confidence expected in the 21 st century.
The rest of this DSc thesis is made up of published articles, as listed in the PDF attached to this record.